Validity and practicality of ecosystem e-modules integrated with local wisdom to improve students' SCA and critical thinking skills - Meli Marlina; Wan Syafi’i; S. Suwondo (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The 21st century education requires students to master the skills of Social Culture Awareness (SCA) and critical thinking, but the lack of use of local wisdom-based teaching materials is an obstacle in its achievement. This study aims to determine the validity and practicality of ecosystem e-modules integrated with local wisdom to improve students' SCA (Social Cultural Awareness) and critical thinking skills. The study was place at SMA Negeri 12 Pekanbaru and the Riau University Postgraduate Campus. Research and development refer to this specific kind of study.  The three phases of the ADDIE model—analysis, design, and development—form the basis of the chosen research methodology.  Questionnaires designed to assess feasibility and validity were used as data collecting tools.  findings from the e-module practicality test by instructors, the one-to-one test, and the small-scale test all came out with very practical ratings of 98.72%, 95.85%, and 98.61%, respectively, while the validation findings came out with a highly valid category score of 93.71%.  Based on these findings, the created e-module is a great tool for enhancing students' SCA and critical thinking abilities. E-Modules are recommended as alternative teaching materials that can support the development of students' SCA and critical thinking skills, as well as strengthen learning rooted in local wisdom.